The Influence of Understanding Science Concepts, Critical Thinking Skills, and Scientific Literacy on Scientific Attitudes Class IV Primary School Students - Sekaringtyas, Tunjungsari; Suyono, Suyono; Hadi, Waluyo (Journal of Ecohumanism, 2024)
Background: This research aims to analyze whether there is a direct or indirect influence between understanding science concepts, critical thinking skills, and scientific literacy on the scientific attitudes of elementary school students. This research is quantitative research with a survey method using path analysis techniques. The research population was elementary school students in the Pisangan Timur area, East Jakarta, totaling 134 students. Data collection was carried out through questionnaires and interviews. The results of the path coefficient calculation show that Py1 = 0.221, Py2 = 0.305, Py3 = 0.422, P21 = 0.249, P31 = 0.405, P32 = 0.305. This value is smaller than the significance level of 0.05, so H0 is rejected. Based on these results, it can be concluded that there is a direct influence between understanding science concepts, critical thinking, and scientific literacy on the scientific attitudes of elementary school students. The better the scientific attitude that students have, the better their achievements will be because they are equipped with a good understanding of concepts, critical thinking, and scientific literacy. Objective: In general, this research aims to obtain information about the influence of Understanding Natural Science Concepts, Critical Thinking, and Scientific Literacy on the Scientific Attitudes of Class IV Elementary School Students. The specific objectives to be achieved are to obtain data about 1) conceptual understanding, 2) critical thinking, 3) scientific literacy, and 4) scientific attitudes of class IV elementary school students. Based on these data, this research aims to analyze the extent to which: (1) The Direct Influence of Understanding Concepts on the Scientific Attitudes of Class IV Elementary School Students, (2) this research study, the aim is to obtain information about the influence of understanding science concepts, critical thinking, and scientific literacy on the scientific attitudes of Class IV Elementary School students. The specific objectives to be achieved are to develop data regarding 1) understanding of concepts, 2) critical thinking, 3) scientific literacy, and 4) scientific attitudes of students in class IV Elementary School. Based on the preliminary data, this research aims to analyze the following: (1) Direct influence of Concept Understanding on the Scientific Attitudes of students in class IV Elementary School, (2) Direct influence of Critical Thinking Skills on the Scientific Attitudes of students in class IV Elementary School, (3) Direct influence of Science Literacy on the Scientific Attitudes of Class IV Elementary School students, (4) Direct influence of Understanding of Concepts on Critical Thinking Ability, (5) Direct influence of Understanding of Concepts on Scientific Literacy, (6) Direct influence of Critical Thinking Ability on Scientific Literacy. Theoretical Framework: A scientific attitude is very important for students who are in the process of studying science, and who are also expected to be able to develop science in the future. A scientific attitude is also important for students because it will influence student learning achievement. Facts show that the scientific attitude of students in Indonesia is still low. One global indicator is that the average PISA score for Indonesian students in 2022 is only 383, below the international average score. Therefore, it is important to improve students' scientific attitudes. One effort to improve students' scientific attitudes is to look for factors that can significantly improve scientific attitudes. Data will be collected using valid and reliable instruments. The data analysis technique that will be used is path analysis. It is hoped that the results of this research will be useful for teachers and other stakeholders as a basis for improving the scientific attitudes of Indonesian students. The target outputs of this research are 1) scientific articles to be published in reputable international journals, and 2) intellectual property rights from the research instruments developed. Method: This research uses a quantitative approach, survey methods, and path analysis techniques. Variables in path analysis consist of exogenous variables (independent variables) and endogenous variables (dependent variables). The three independent variables are Conceptual Understanding (X1), Critical Thinking (X2), and Scientific Literacy (X3), while the dependent variable is Scientific Attitude (Y). The participants in this research were 134 students. By the research problem, research objectives, and research variables, there are four data required in this research, namely data related to Understanding Science Concepts, Critical Thinking Skills, Scientific Literacy, and Scientific Attitudes in class IV elementary school students. Data on Understanding Science Concepts, Critical Thinking, and Scientific Literacy were collected using multiple choice objective tests and essays, and data on Scientific Attitudes were collected using a questionnaire using a Likert scale. Statistical analysis in this research was carried out to understand the direct and indirect effects of variable X (Understanding of Science Concepts, Critical Thinking, and Scientific Literacy) on variable Y (Scientific Attitude) using path analysis. Results and Discussion: It is known that there are three causal relationship structures, namely: (a) The first relationship structure, namely the variable causing Understanding of Science Concepts, Critical Thinking, and Scientific Literacy to the variable resulting from Scientific Attitude. This first relationship structure answers the first, second, and third research hypotheses, namely 1) the direct influence of Understanding Science Concepts on Scientific Attitudes, 2) the direct influence of Critical Thinking on Scientific Attitudes, 3) the direct influence of Scientific Literacy on Scientific Attitudes, (b) Structure the second relationship, namely the variable causing Understanding of Science Concepts and Critical Thinking to the variable resulting from Scientific Literacy. This second relationship structure can answer the fifth and sixth hypotheses, namely 1) the direct influence of Understanding Natural Science Concepts on Scientific Literacy, 2) The direct influence of Critical Thinking on Scientific Literacy, (c) The third relationship structure, namely the causal variable of Understanding Natural Science Concepts on the Thinking variable. Critical. This third relationship structure can answer the fourth hypothesis, namely the influence of Understanding Science Concepts on Critical Thinking. It is important to know that this research has limitations, namely that educators still pay attention to the aspects of students in their learning process at school. Research Implications: Found a direct influence on understanding science concepts, critical thinking, and scientific literacy on scientific attitudes. Therefore, there are research implications that are explained, such as the influence of the independent variables, namely Understanding Science Concepts, Critical Thinking, and Scientific Literacy, which have been proven to be true. Each of these three variables can be used as a determinant of Scientific Attitude. The three determining factors, namely Understanding Natural Science Concepts, Critical Thinking, and Scientific Literacy, are the determining factors in Scientific Attitude and have been tested in this research. It is hoped that the results of this research can be used as a reference for relevant research in the future, especially those related to the formation of students' scientific attitudes in elementary schools. Originality/Value: Students who have a good understanding of science concepts can form good scientific attitudes as well. Students are also required to have good critical thinking skills to be able to form a good scientific attitude because one of the characteristics of someone who has a good scientific attitude is when that person has good critical thinking skills too, critical thinking skills will stimulate Students' cognitive reasoning in acquiring knowledge, critical thinking is also an aspect that needs to be developed in 21st-century learning. Good critical thinking skills will develop a good scientific attitude, students are expected to be able to be sensitive to the environment around them. Next, it is important to see how much scientific literacy students have. The ability of students to recognize appropriate and related knowledge, the breadth of information related to the knowledge in question, and the teaching and reading materials used by students in learning. This situation will greatly influence the formation of students' scientific attitudes.